The Influence Of Compensation And Leadership Style On Employee Performance At PT. Gerbang Mandiri Sukses Jakarta - Witak, Margareta Yelsiana Ina; Vidada, Irwin Ananta; Aliudin, Raden Muhammad Tedy; Rini, Ratih Setyo (SEAN Institute, 2025)
This study examines the influence of compensation and leadership style on employee performance. Using a quantitative approach, data were collected from a saturated sample of 32 employees at PT. Gerbang Mandiri Sukses Jakarta through questionnaires, observations, interviews, and documentation. Validity and reliability tests confirmed the robustness of the research instruments. Multiple linear regression analysis showed that both compensation and leadership style have a significant and positive impact on employee performance, with leadership style demonstrating a stronger influence. The results highlight the importance of fair compensation systems and effective leadership in enhancing productivity and achieving organizational goals. This research provides practical insights for improving human resource management strategies, particularly in creating a motivated and high-performing workforce. These findings emphasize the critical role of strategic HR practices in supporting organizational success.